AKUN MEDIA SOSIAL INSTAGRAM @KONTRIBUTORJAKARTA SEBAGAI SARANA INFORMASI TENTANG JABODETABEK - Prima Hasiholan, Togi; A. Malikidin, Dian Ardika; Azizah, Nur (Aksara Public, 2020)
Indonesia is currently very rapidly enjoying the development of communication and information technology, the internet network which is a technology product that is very rapidly used throughout the world, including in the country of Indonesia. The use of social media applications in Indonesia based on some existing research agency data always puts Indonesia as the largest country in the use of social media, including social media Instagram. The massive use of Instagram social media has made several news contributors in Jabodetabek create an Instagram account to be a means of information about Jabodetabek that is always up to date and honest in broadcasting. It is not easy to get the appropriate results in the expectations, if without the previous strategy. The visual communication process strategy can be a powerful weapon to get the maximum results that the story sounds to date.